Cultura hip hop: os movimentos corporais do breaking nas batalhas do Grupo Amazon B. Boy - COSTA, Ana Carolina Rosario da (2021)
It is known that one of the objectives of breaking is to achieve superior performance, that is, to gather all the qualities of its participants so that they can make a difference in their environment. It is noteworthy that the practice of breaking dance promotes over time the corporal mastery and psychological knowledge of the practicing individual, offering a feeling of well-being, personal satisfaction, emphasizing the importance of individual and collective competence. Thus the present research had the objective of conducting a study on the influence of Breaking dance on the body movements of the members of the Amazon B. Boy group in Belém do Pará. In addition, the approach discussed a brief history about hip hop culture in Brazil and the Amazon B. Boy Group, identifying which body contributions the break dance provides to practitioners. The methodology used in the research was bibliographical in addition to a field research. The research used authors that were essential as theoretical references for the development of the study, among them, Alves (2001) concerning the street dance; Canclini (1995) on the multicultural conflicts of globalization; Felix (2005) on Hip Hop culture; Fochi (2007) on Brazilian Hip Hop and its characteristics as a social movement; Garaudy (1980) on dance and Herschmann (1978) refers to Funk and Hip Hop. As a conclusion it was possible to observe the importance of the questions related to breaking dance and the strategies of battles used by the group Amazon B.boy of Belém do Pará.